Staff support services Room by the side of the road - Smoot, Fred L.; Wells, Donald E. (1985)
Staff Support Services, as done at Emory University Hospital, Atlanta, Georgia, uses the neutrality of the Department of Pastoral Services to meet the support needs of its staff. This model has evolved out of the concern of many departments to centralize and symbolize the availability of these various support services to hospital employees. Using a "shepherding model", Emory's Staff Support Services works both within and outside of the "room by he side of the road".
Keywords: Hospital Employee; Pastoral Service; Staff Support; Staff Support Service; Support Service